THE IMPACT OF FISCAL POLICY AND FOREIGN DIRECT INVESTMENT ON ECONOMIC GROWTH IN EIGHT MEMBER COUNTRIES OF THE ORGANIZATION OF ISLAMIC COOPERATION (OIC) - Daulay, Aisyah Futri Utami; Sihombing, Sulaiman (Islamic Economics Program, Faculty of Islamic Economics and Business, 2025)
This study provides evidence on how fiscal policy, proxied by government expenditure, and foreign direct investment (FDI) affect real economic growth in the D-8 group of Organization of Islamic Cooperation (OIC) member countriesBangladesh, Egypt, Indonesia, Iran, Malaysia, Nigeria, Pakistan, and Turkey. It responds to mixed findings in the OIC literature by focusing on a more homogeneous cooperation bloc and by quantifying both the statistical and economic significance of these policy variables. The analysis uses annual panel data for 2017–2021, combining World Development Indicators and official national statistics. Economic growth is measured as the annual real GDP growth rate, while fiscal policy and FDI are measured as government expenditure (% of GDP) and net FDI inflows (% of GDP), respectively. A linear panel-data model is estimated, and specification tests (Chow and Hausman) clearly support a Fixed Effects Model that controls for time-invariant country heterogeneity. The Fixed Effects estimates show that both government expenditure and FDI have positive and statistically significant impacts on growth (p < 0.01). The coefficient for government expenditure is β₁ = 1.60, implying that a 1 percentage-point increase in government expenditure as a share of GDP is associated with an increase of about 1.60 percentage points in real GDP growth, ceteris paribus. The coefficient for FDI is β₂ = 2.19, indicating that a 1 percentage-point increase in net FDI inflows relative to GDP is associated with an increase of roughly 2.19 percentage points in real GDP growth. The model explains around 61% of the within-country variation in growth over time. The study provides clear evidence that, in D-8 countries, both higher government expenditure and greater FDI inflows are not only statistically significant but also economically important drivers of growth during 2017–2021. These results position the D-8 within the more optimistic strand of the OIC literature on fiscal policy and FDI, and they underscore the potential of productive public spending and foreign capital to support post-crisis recovery and medium-term development in this cooperation bloc.